Investigation of the Heat Transfer Mechanism of CO2-Assisted Steam Injection via Experimental and Simulation Evaluation - Xu, Zhengxiao; Li, Zhaomin; Li, Binfei; Li, Songyan; Lu, Teng; Wu, Mingxuan; Bai, Hao (Frontiers in Energy Research, 2020)
Steam injection is an important process for the thermal recovery of heavy oil reservoirs. As a non-condensable gas CO2-assisted steam injection can not only improve the development effect but also reduce carbon emissions. In this study, the simulation method was combined with the experimental method. Based on an experiment using steam condensation with or without CO2, the influence of the condensation mode on steam heat transfer was considered. The effect of changes in the steam flow rate on phase transition and steam quality were analyzed. The heat transfer effects of the gas-steam mixture with different contents of CO2 were compared. The results show that the surface condensation mode changes from dropwise condensation to film condensation with the addition of CO2, and the average temperature of the condensation block decreases by 20.05%. With increases in the steam flow rate, the quality of steam increases, and the heat transfer coefficient of steam on the condensation surface increases. With increase in CO2 content, the temperature of the gas-steam mixture decreases, and the inhibition effect on steam heat transfer is more obvious.